If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + 9 + -2z = 33 + -2z Reorder the terms: 9 + 4z + -2z = 33 + -2z Combine like terms: 4z + -2z = 2z 9 + 2z = 33 + -2z Solving 9 + 2z = 33 + -2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2z' to each side of the equation. 9 + 2z + 2z = 33 + -2z + 2z Combine like terms: 2z + 2z = 4z 9 + 4z = 33 + -2z + 2z Combine like terms: -2z + 2z = 0 9 + 4z = 33 + 0 9 + 4z = 33 Add '-9' to each side of the equation. 9 + -9 + 4z = 33 + -9 Combine like terms: 9 + -9 = 0 0 + 4z = 33 + -9 4z = 33 + -9 Combine like terms: 33 + -9 = 24 4z = 24 Divide each side by '4'. z = 6 Simplifying z = 6
| 4(x-7)=3(2x-1)+3 | | 5x-44=-8 | | 21x^2+19x-2= | | 22+9x=-12+8x | | 6u^2+48u+72= | | 7p+-3p=-4p+16 | | x=6-25 | | 15-4x=9-5x | | -10x=190 | | 7+2x=x+8 | | 8(-3v-7)=20-5v | | x=1/2(0+28.5)7 | | 1(4x+2)=4x-12(x-1) | | 4x+2=4+3x | | 1.2(5x-4)=3.6x-12(x+1) | | 7=1/2(0+28.5)x | | 2u^2+2u-60= | | -8+x=-2x-1 | | 10-5(6-2x)=6-(16-20x) | | -1.8=1.6x | | 4w-6w^3= | | x^2+69x-1080=0 | | -7+5(-4+r)=-12 | | 2(12x-5)=3(8x+2)-16 | | 7p+-4+-3p=-4p+2+10 | | 6+8(1-3m)=62 | | 6(n-3)=-66 | | -37=6(r-8)-7 | | -80=n+10 | | 7+5(b+4)=-13 | | ydx+(1-x)dy=0 | | 4+8=7 |